China-Australia Trade Relations and China’s Barley Imports - Jingyi Liu; Xiande Li; Junmao Sun (Agriculture, 2023)
The high concentration of China’s barley import sources determines that China’s barley import trade is vulnerable to the impact of tariff policy adjustment. In particular, in 2020, China implemented anti-dumping and anti-subsidy policies against Australia, the largest source of barley imports. Therefore, whether China’s barley import trade will face import risks due to the adjustment of tariff policy has become a question worth discussing. Based on the above background, this study uses the partial equilibrium model to explore the impact of China’s adjustment of tariff policy on imported barley from Australia on China’s barley industry under the changing trade relations between China and Australia. Through analyzing the feasibility of developing domestic barley industry and expanding barley import sources, further explore strategies to deal with barley import trade risks. The results show that: Under the three import tariff adjustment simulations, the total import volume of China’s barley shows a downward trend, and the import price increases to varying degrees. However, the relatively small increase in domestic production suggests that the domestic barley market is less able to cope with the risk of a sharp drop in imports. At the same time, affected by the adjustment of tariff policy, some Chinese consumer demand is difficult to satisfy. China can deal with trade risks by implementing an import diversification strategy.